Tryin′ to Make it Real, But Compared to What? - Lambek, Michael (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1991)
I explore how comparison might look from a hermeneutic perspective. I use the discussion as a means to clarify some of the positive attributes of hermeneutics and to respond to some of the criticisms and misunderstandings to which interpretive anthropology has been subject.